An Acute Ischemic Stroke Classification Instrument That Includes CT or MR Angiography: The Boston Acute Stroke Imaging Scale - Torres-Mozqueda, F.; He, J.; Yeh, I.B.; Schwamm, L.H.; Lev, M.H.; Schaefer, P.W.; González, R.G. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: A simple classification instrument based on imaging that predicts outcomes in patients with actute ischemic stroke is lacking. We tested the hypotheses that the Boston Acute Stroke Imaging Scale (BASIS) classification instrument effectively predicts patient outcomes and is superior to the Alberta Stroke Program Early CT Score (ASPECTS) in predicting outcomes in acute ischemic stroke.MATERIALS AND METHODS: Of 230 prospectively screened, consecutive patients with acute ischemic stroke, 87 had noncontrast CT (NCCT)/CT angiography (CTA), and 118 had MR imaging/MR angiography (MRA) at admission and were classified as having major stroke by BASIS criteria if they had a proximal cerebral artery occlusion or, if no occlusion, imaging evidence of significant parenchymal ischemia; all of the others were classified as minor strokes. Outcomes included death, length of hospitalization, and discharge disposition. BASIS was compared with ASPECTS (dichotomized > or ≤7) in 87 patients who had NCCT/CTA.RESULTS: BASIS classification by NCCT/CTA was equivalent to MR imaging/MRA. Fifty-six of 205 patients were classified as having major strokes including all 6 of the deaths. A total of 71.4% and 15.4% of major and minor stroke survivors, respectively, were discharged to a rehabilitation facility, whereas 14.3% and 79.2% of patients with major and minor strokes were discharged to home. The mean length of hospitalization was 12.3 and 3.3 days for the major and minor stroke groups, respectively (all outcomes, P < .0001). In 87 NCCT/CTA patients, BASIS and ASPECTS agreed in 22 major and 44 minor strokes. BASIS classified 21 patients as having major strokes who were classified as having minor strokes by ASPECTS. The BASIS major/ASPECTS minor stroke group had outcomes similar to those classified as major strokes by both instruments.CONCLUSIONS: The BASIS classification instrument is effective and appears superior to ASPECTS in predicting outcomes in acute ischemic stroke.